Türk Milliyetçiliğinin Evrimi - Yesevi, Çağla Gül (My University, 2012)
Bu çalışmada, Türk milliyetçiliğinin, Osmanlı Devleti’nde başlayan modernleşme hareketleriyle bağlantısı üzerinde durulacaktır. Yeni Osmanlılar, Jön Türkler ve İttihat ve Terakki’nin Türk milliyetçiliğinin gelişmesi üzerindeki etkilerine değinilecektir. Türk milliyetçiliği, Cumhuriyet dönemiyle sınırlandırılmayacaktır. Cumhuriyet döneminde, Türk milliyetçiliğinin sınıflandırması yapılacaktır. Bu bağlamda, Kemalist milliyetçilik, Türkçülük, Türk-İslam sentezi ve Ulusalcılık açıklanacaktır.

This study will examine the connection between the Ottoman modernization process and Turkish nationalism. The research highlights the emergence of Turkish nationalism with the contribution of political thoughts of Young Ottomans, Young Turks and policies of the Community of Union and Progress. Also, the study will examine the main parameters of Turkish nationalism in the Republican era. This period will be classified as Kemalist Nationalism, Turkism, the Turkish-Islam Thesis and Ulusalcılık (neo-nationalism.)
Evolution of Turkish nationalism
Keywords: Türk Milliyetçiliği; Gelişim; Sınıflandırma; Turkish Nationalism; Development; Classification